Effects of EPA and DHA on in vitro ruminal biohydrogenation of 18-carbon fatty acids in sheep - Toral P.G.; Hervás G.; Carreño D.; Leskinen H.; Belenguer A.; Shingfield K.J.; Frutos P. (Innovation for sustainability in sheep and goats, 2019)
Marine lipid supplements have been used to inhibit the ruminal saturation of trans-11 18:1, with the final goal of enhancing cis-9 trans-11 conjugated linoleic acid (CLA) concentration in milk and meat. This response would be largely explained by the effects of n-3 very long chain polyunsaturated fatty acids (PUFA) on the last step of biohydrogenation (BH). In cows, docosahexaenoic acid (DHA, 22:6n-3) has been suggested to be a stronger inhibitor of trans-18:1 hydrogenation than eicosapentaenoic acid (EPA, 20:5n-3), but information about changes in individual 18:1 isomers is very limited, and no reports are available in sheep. This in vitro study was therefore conducted to compare the impact of EPA and DHA on the BH of 18-carbon fatty acids in ovine, using batch cultures of rumen microorganisms and cannulated ewes as inocula donors. The two PUFA were added at a dose of 2% incubated DM and effects were examined after 24 h of incubation. The DHA treatment led to the greatest concentration of trans-18:1 in digesta, but this was mainly accounted for by accumulation of metabolites from alternative BH pathways (e.g, trans-9, -10, -12 and -15 18:1), while the inhibition of trans-11 18:1 saturation was comparable with both PUFA. The saturation of cis-18:1 was constrained too, particularly by DHA, whereas EPA seemed to have specific effects on 18:3n-3 metabolism. Changes in oxo-FA concentrations suggested that ruminal hydration (an alternative metabolic pathway to BH) was also affected by PUFA treatments.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)